Medieval literature for children - Kline, Daniel T. (New York : Routledge, 2003)
An anthology of medieval children's literature, arranged in various categories and interspersed with scholarly commentary.
pt. 1. Didactic and moral literature -- pt. 2. Courtesy and conduct literature -- pt. 3. Educational and instructional literature -- pt. 4. Religious literature -- pt. 5. Entertainment and popular literature.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Literature, Medieval; Children's literature; Electronic books